Multi-objective scheduling of Scientific Workflows in multisite clouds - Liu, Ji; Pacitti, Esther; Valduriez, Patrick; de Oliveira, Daniel; Mattoso, Marta (Future generation computer systems, 2016)
Clouds appear as appropriate infrastructures for executing Scientific Workflows (SWfs). A cloud is typically made of several sites (or data centers), each with its own resources and data. Thus, it becomes important to be able to execute some SWfs at more than one cloud site because of the geographical distribution of data or available resources among different cloud sites. Therefore, a major problem is how to execute a SWf in a multisite cloud, while reducing execution time and monetary costs. In this paper, we propose a general solution based on multi-objective scheduling in order to execute SWfs in a multisite cloud. The solution consists of a multi-objective cost model including execution time and monetary costs, a Single Site Virtual Machine (VM) Provisioning approach (SSVP) and ActGreedy, a multisite scheduling approach. We present an experimental evaluation, based on the execution of the SciEvol SWf in Microsoft Azure cloud. The results reveal that our scheduling approach significantly outperforms two adapted baseline algorithms (which we propose by adapting two existing algorithms) and the scheduling time is reasonable compared with genetic and brute-force algorithms. The results also show that our cost model is accurate and that SSVP can generate better VM provisioning plans compared with an existing approach. •A multi-objective cost model that includes execution time and monetary costs.•A Single Site VM Provisioning (SSVP) approach, to generate VM provisioning plans.•ActGreedy, an efficient scheduling algorithm for SWf execution in multisite cloud.•An extensive experimental evaluation in Microsoft Azure using the SciEvol SWf.